Validation of the Double Mediation Model of Workplace Well-Being on the Subjective Well-Being of Technological Employees - Chang, Shu-Ya; Hsu, Hsiang-Chen (Frontiers in Psychology, 2022)
In recent years, the workplace well-being has been an important research topic. It can help promote employee’s welfare, thereby bringing valuable personal and organizational outcomes. With the development of technology, the technology industry plays an important role in Taiwan. Although the salary and benefits provided by the technology industry are better than other industries, the work often requires a lot of time and effort. It is worth paying attention whether a happy workplace will bring subjective well-being for the technology industry in Taiwan. This study uses subjective well-being as a dependent variable to explore the influence of workplace well-being, job involvement, and flow on subjective well-being. The research was conducted using a questionnaire survey. The questionnaire survey included 256 employees in the technology industry in the Nanzi Processing Zone in Kaohsiung City, Taiwan. This study used multivariate and structural equation models for data analysis. The study results found that workplace well-being, flow, and job involvement have a positive and significant impact on subjective well-being. In addition to having a direct impact on subjective well-being, flow is also a significant mediating variable from workplace well-being to subjective well-being. Job involvement also affects subjective well-being through flow, which means that the state of selflessness at work is the most important factor affecting subjective well-being. Finally, the research results can provide certain empirical references for government departments and the science and technology industry.